Oxidative stress related changes in the brain of hypercholesterolemic rabbits - KARTAL ÖZER, NESRİN (WILEY, 2008)
In recent years, there has been increasing evidence that cholesterol plays a role in the pathology of Alzheimer disease. Since hypercholesterolemia was reported to increase the levels of reactive oxygen species and Alzheimer disease has clearly involved an oxidative component, it is possible that hypercholesterolemia is via increased oxidant production facilitating the disease development of the neurodegenerative disease. Therefore, we tested in an established model of enhanced cholesterol feed in rabbits the effects of serum cholesterol increase on oxidative stress parameters as well in serum as in the brain. In addition to that we tested the effects of vitamin E on the cholesterol-induced oxidative stress. Since Alzheimer disease is largely connected with increased protein oxidation whereas cholesterol is rather connected with lipid peroxidation processes, we tested both protein carbonyl levels and the formation of malondialdehyde, a marker of lipid peroxidation. We could clearly demonstrate an increase in serum malondialdehyde due to high cholesterol feeding, which is accompanied by an increase in protein oxidation parameters in the brain, especially in the hippocampus. Therefore, we suggest that specific neuropathological changes occur during the feeding of hypercholesterolemic diet.
Keywords: Hypercholesterolemia; oxidative stress; protein oxidation; protein carbonyls; Alzheimer disease; vitamin E; VITAMIN-E CONSUMPTION; ALZHEIMERS-DISEASE; PROTEASOME INHIBITION; OXIDIZED PROTEINS; CORONARY-DISEASE; CHOLESTEROL; ATHEROSCLEROSIS; INFLAMMATION; CELLS; RISK